Prosodic Prominence and Focus: Expectation Affects Interpretation in Samoan and English - Calhoun, Sasha; Wollum, Emma; Kruse Va’ai, Emma (Language and speech, 2021)
This paper looks at the perception of prosodic prominence and the interpretation of focus position in the unrelated languages, Samoan and English. In many languages, prosodic prominence is a key marker of focus, so it is expected that prosodic prominence would affect judgments of focus position. However, it is shown that focus position, in turn, influences the perception of prosodic prominence according to language-specific expectations about the alignment between focus position and nuclear accent placement. Two sets of parallel perception experiments in Samoan and English are reported. In the first, participants judged the most prosodically prominent word in sentences which varied in syntactic construction (cleft/canonical) and intended stress position (subject/object). In both languages, participants were more likely to choose the intended stressed word if it was in the focus position. However, this effect was much larger in Samoan, which fits with its relatively lower functionality of prosodic prominence. In the second experiment, participants were asked to choose which question had been asked, consistent with subject or object focus. It was found that in both languages, participants weighted syntactic and prosodic cues to focus in line with expectations from their language. These findings have implications for how we conceive the role of prosodic prominence in speech processing across languages.